Applying wind patterns and land use to estimate the concentrations of airborne pollen of herbaceous taxa in a statistical framework - Picornell, Antonio; Ruiz-Mata, Rocío; Rojo, Jesús; Oteros, Jose; Recio-Criado, María Marta; Gálvez-Montañez, Enrique de; Trigo-Pérez, María del Mar (Elsevier, 2023)
Airborne pollen concentrations are influenced by wind direction, wind speed, temperature and rainfall among other meteorological variables, but they are conditioned by local land use. Combining land use and wind frequencies within a single variable would allow the estimation of the contribution of the emission sources to the airborne pollen detected. The aim of this study was to develop this new variable and to compare its relevance in estimating airborne pollen concentrations of anemophilous (i.e. wind pollinated) herbaceous taxa versus other meteorological predictors. The airborne pollen concentrations of some herbaceous pollen types were studied in Malaga, Spain (1992–2020). The land-use surfaces were combined with the daily wind direction frequencies to develop an index. This index was relevant for estimating daily airborne pollen concentrations in random forest frameworks since high pollen concentrations were detected on days with high index values. However, the relationship between the index and the pollen concentrations was not linear due to the influence of other variables. Overall, this index constitutes an easy-to-use approach to integrate both land use and wind frequencies in pollen models, and it can be applied to other sampling locations and pollen types.
Keywords: Meteorología; Polen; Botánica; Fisiología vegetal; Aerobiology; Meteorology; Pollen; Emission sources; Random forest